Religious Education in Public Schools: Study of Comparative Law - Martínez López-Muñiz, José Luis; De Groof, Jan; Lauwers, Gracienne (Yearbook of the European Association for Education Law and Policy, 2006)
Europe is going through a sort of "social revolution" with the influence of the church and religious instruction in state schools being open to discussion. Critics claim that providing religious instruction in state schools violates the constitutional separation of church and state. And yet, despite an alleged separation of church and state, in most countries, the church continues to play a considerable public role, especially in education. This publication is a compilation of studies on religious instruction in state schools. It describes the diversity between states and analyzes the legislative basis of religious instruction in various countries. Whereas in some countries, religious instruction in state schools is optional or compulsory with the possibility to opt out, in other countries religious instruction is banned from state schools. The comparative analyses in this book will be of great value to researchers in educational research and to educational policymakers. The chapters are written in the English, French, German, Italian and Spanish language.